Efektivitas Penegakan Hukum Tindak Pidana Pemilu Melalui Media Sosial - Fauziyah, Rezza; Raharjo, Agus; Wahyudi, Setya (Syntax Corporation, 2025)
The enforcement of election law violations through social media in the legal area of Bawaslu Purworejo still faces several challenges, hindering its effectiveness. This study aims to analyze the effectiveness of election law enforcement through social media and the obstacles faced by Bawaslu Purworejo in addressing election violations in the digital age. The method used is an empirical juridical approach with field studies and interviews with relevant parties. The results show that, despite efforts to address violations, limitations in securing digital evidence, inter-agency coordination, and the unpreparedness of forensic infrastructure are the main obstacles. Furthermore, the gap between legal substance and digital realities, as well as low digital legal literacy, also affects the effectiveness of law enforcement. This study recommends strengthening regulations on digital campaigns, digital forensics training for law enforcement officials, and organizing digital election literacy to improve the understanding of the public and officials.